The Bahamas. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Bahamas Delegation of 2022 are identified, focus to needs and interests of the country such as; IICA supported the Commonwealth of The Bahamas with financial and logistical resources at critical international meetings; encourage nationals and tourists to support local agriculture and producers through the “Buy Fresh, Buy Local, Buy Bahamian” campaign; continues to provide logistical and technical support to The Bahamas Network of Rural Women Producers (BAHNROP); it supported a National Validation Workshop to assess the readiness of The Bahamas to carry out climate change programming at the national level; finally IICA was selected to participate in events aimed at increasing investment into The Bahamas and establishing partnerships with local entrepreneurs and small businesses.